Analisis Pengakuan Pendapatan Kontrak Berdasarkan PSAK 115 Pada PT Syma Berkah Indonesia - Deviyanti Sofia Rachman; Siti Sundari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Revenue is a variable that companies consider when deciding to transact with their customers. Therefore, in reaching an agreement with a customer, the company generally binds the economic relationship with the contract agreement to determine the transaction price of the transfer of goods or services. Based on PSAK 115, it is stated that revenue is regulated in five principles, namely: (1) identifying contracts with customers; (2) identifying the obligation to perform in the contract; (3) determining transaction prices; (4) allocating transaction prices to implementation obligations; and (5) recognize revenue when (or during) the entity fulfills its performance obligations. If the company has fulfilled the five stages of PSAK 115, the company can recognize revenue. On the other hand, if it does not meet any of them, the company cannot recognize revenue. This study is aimed at finding out the conformity between the recognition of PT. Syma Berkah Indonesia which is one of the contractor service companies in the city of Surabaya with PSAK 115. The analysis method used by the researcher is a qualitative descriptive method to explain the data collected from the company both from the results of interviews, observations, and documentation. Based on the analysis conducted by the researcher, it was stated that PT. Syma Berkah Indonesia implements PSAK 115 to recognize that contract income is considered appropriate.